PEMBERIAN JENIS PAKAN YANG BERBEDA TERHADAP PERTUMBUHAN KEPITING BAKAU (Scylla serrata) - Klau, Marini Cladita; Linggi, Yulianus; Djonu, Asriati (Nusa Cendana University, 2025)
The research was conducted in Tarus Village (Manikin Beach), Kupang Tengah District, Kupang Regency. The location of this research was determined by considering that the waters in Kupang Regency, especially Tarus Village (Manikin Beach). The treatments tested were the provision of different types of feed, Treatment A: Feeding snails, Treatment B: Feeding mangrove shells, Treatment C: Feeding trash fish (tembang fish), Treatment D: Feeding chicken stomachs. The parameters measured in this study were absolute weight, daily weight and survival. Based on the research and research results the provision of different feeds significantly affected growth, both weight, but did not affect survival and the best feed for growth was shown in treatment A with the use of snail feed which resulted in absolute weight growth of 29.00 g, daily growth of 0.48 g% / h. While for survival reached 100% all treatments.